Relationship between internet addiction and depression among young adults in Dhaka, Bangladesh (Dhaka University Journal of Biological Sciences, 2025)
This study explored the relationship between internet addiction and depression among young adults in Dhaka. A conveniently selected sample of 200 participants aged 18-35 completed the Internet Addiction Test (IAT) and Patient Health Questionnaire-9 (PHQ-9), along with several demographic questions. Descriptive statistics were used to summarise participant demographics, while a series of logistic regressions examined the association between internet addiction and depression. Results indicated a high prevalence of both internet addiction (minimal user: 20.0%; moderate to excessive user: 80.0%) and depression (minimal or no depression: 16.0%; mild to severe depression: 84.0%) among the study sample. The study found a significant association between internet addiction and depression, with moderate to excessive internet users being 3.7 times more likely to experience depression compared to minimal users. These findings emphasise the need for increased awareness about internet use among young adults to mitigate the risk of associated depression.Dhaka Univ. J. Biol. Sci. 34(1): 85-95, 2025 (January)